Relationship of Bactericidal Permeability Increasing Protein (BPI) Polymorphysm rs1341023, rs5743507, Tumor Necrosis Factor Alpha (TNF-α) rs361525, rs1800629 with Neonatal Sepsis - Afdal, Afdal; Jamsari, Jamsari; Yanwirasti, Yanwirasti; Rukmono, Prambudi (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Neonatal sepsis is a problem in the field of child health because the incidence is increasing every year and often ends in death. This study aimed to investigate the relationship between TNF-α and BPI gene polymorphisms with neonatal sepsis. Methods: PCR and sequencing examinations were performed on 60 DNA samples consisting of 30 samples of neonatal sepsis and 30 samples of non-neoptic sepsis. Furthermore, data in the form of DNA mutation tables were statistically processed by univariate, bivariate, and multivariate analysis. It is considered meaningful if p<0.05. Result: The results showed that BPI rs1341023, rs5743507 and TNF-α rs361525, rs1800629 only BPI rs1341023 and TNF-α rs1800629 were mutated. Of the two genes, only TNF-α rs1800629 had a significant association with neonatal sepsis (p<0.05). Conclusion: This study proved that the TNF-α rs1800629 mutation was the most important polymorphism in the occurrence of neonatal sepsis (p<0.05). Keywords: BPI, TNF-α, Neonatal, Polymorphism, Sepsis